Pengaruh Gaya Kepemimpinan dan Budaya Organisasi Terhadap Disiplin Kerja Pegawai : Studi Kasus pada Kantor DPMPTSPTK Kabupaten Tasikmalaya - Silviana Nurhilman; Rita Tri Yusnita; Arif Arif (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research aims to determine the influence of leadership style and organizational culture on employee work discipline at the DPMPTSPTK Office, Tasikmalaya Regency. This research uses quantitative research with a descriptive approach and verification research. The types of data used are primary data and secondary data, with a research sample of 57 respondents from employees of the Tasikmalaya Regency DPMPTSPTK Office, and using a saturated sample method. The data analysis tool used in this research is IBM SPSS Version 25. Data collection techniques use literature studies, interviews, questionnaires. The research results show that leadership style and employee organizational culture simultaneously have a significant effect on employee work discipline. Leadership style partially has a significant effect on employee work discipline. Organizational culture partially has no significant effect on employee work discipline.